Real-Time Ligand Binding of Fluorescent VEGF-A Isoforms that Discriminate between VEGFR2 and NRP1 in Living Cells. Issue 10 (18th October 2018) - Peach, Chloe J.; Kilpatrick, Laura E.; Friedman-Ohana, Rachel; Zimmerman, Kris; Robers, Matthew B.; Wood, Keith V.; Woolard, Jeanette; Hill, Stephen J.
Summary: Fluorescent VEGF-A isoforms have been evaluated for their ability to discriminate between VEGFR2 and NRP1 in real-time ligand binding studies in live cells using BRET. To enable this, we synthesized single-site (N-terminal cysteine) labeled versions of VEGF165 a, VEGF165 b, and VEGF121 a. These were used in combination with N-terminal NanoLuc-tagged VEGFR2 or NRP1 to evaluate the selectivity of VEGF isoforms for these two membrane proteins. All fluorescent VEGF-A isoforms displayed high affinity for VEGFR2. Only VEGF165 a-TMR bound to NanoLuc-NRP1 with a similar high affinity (4.4 nM). Competition NRP1 binding experiments yielded a rank order of potency of VEGF165 a > VEGF189 a > VEGF145 a. VEGF165 b, VEGF-Ax, VEGF121 a, and VEGF111 a were unable to bind to NRP1. There were marked differences in the kinetic binding profiles of VEGF165 a-TMR for NRP1 and VEGFR2. These data emphasize the importance of the kinetic aspects of ligand binding to VEGFR2 and its co-receptors in the dynamics of VEGF signaling. Graphical Abstract: Highlights: VEGF165 a, VEGF121 a, and VEGF165 b were single-site labeled with tetramethylrhodamine NanoBRET quantified that VEGF-A isoforms have similar binding properties at VEGFR2 NRP1 expressed in live cells does not bind VEGF165 b, VEGF121 a, VEGF-Ax, or VEGF111 a VEGFR2 and NRP1 have markedly distinct kinetic profiles binding VEGF165 a-TMR Abstract : Peach et al. have used fluorescent VEGF-A isoforms to demonstrate that they can discriminate between VEGFR2 and its co-receptor NRP1 in real-time ligand binding studies in live cells. This precision chemical biology approach showed that fluorescent VEGF165 a binds more rapidly to NRP1 than VEGFR2.